2014
DOI: 10.1039/c4ra05381h
|View full text |Cite
|
Sign up to set email alerts
|

Conductive nanocomposite hydrogels with self-healing property

Abstract: A flexible, electrically conducting hydrogel with self-healing repeatability can be of use in emerging fields such as soft passive resistors–capacitors and electro-active soft sensor devices, but combining all these properties remains a challenging task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…9b-f. This means that the surface tension remains constant for all samples (samples [1][2][3][4][5], if only composition ratio changes. Without neutraliser, however (sample 6), the contact angle increased dramatically (Fig.…”
Section: Molecular Interactions In Wsrmentioning
confidence: 97%
See 1 more Smart Citation
“…9b-f. This means that the surface tension remains constant for all samples (samples [1][2][3][4][5], if only composition ratio changes. Without neutraliser, however (sample 6), the contact angle increased dramatically (Fig.…”
Section: Molecular Interactions In Wsrmentioning
confidence: 97%
“…Due to the presence of a three-dimensional network, SAPs can absorb and retain a large amount of water increasing in volume a hundred-or thousand-fold without dissolving in the water. SAPs are used in a variety of applications such as medicine, sanitary goods, the food industry and agricultural and horticultural applications [1][2][3][4][5][6]. Despite the capacity of SAPs to absorb large amounts of water, they do not have enough gel strength for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…This result confirmed that the contribution of HB can cause the formation of PAA-based hybrid materials, in which mechanical and other properties could also be changed. 4 …”
Section: Molecular Interactions Within Hydrogelsmentioning
confidence: 99%
“…[1][2][3] As enviro-sensitive materials, hydrogels have been widely used for industrial and biomedical applications due to their unique structure and capabilities. [4][5][6] The properties of a specific hydrogel are extremely important in selecting which materials are suitable for a given application. The suitability of a hydrogel for a given application depends on the mechanical properties that are affected by the environmental conditions such as temperature, pH level and ionic strength, magnetic and electric fields as well as the monomer type and crosslinking agents.…”
Section: Introductionmentioning
confidence: 99%
“…11,27 The incorporation of conducting fillers into a self-healing matrix (e.g. intrinsic self-healing gels 26,[28][29][30][31] and polymers 7,22,32 ) to form selfhealing composites is an attractive strategy to achieve conductors which intrinsically self-heal at ambient temperature. These composites have an advantage that their self-healing function can serve multiple times, promising repeatable recovery of mechanical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%